2006
DOI: 10.1080/02713680600701513
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Anatomy of Laboratory Animal Corneas with a New-Generation High-ResolutionIn VivoConfocal Microscope

Abstract: The Rostock Cornea Module of the HRT II can provide high-resolution images of all corneal layers of rabbits, rats, and mice without sacrificing animals or preparing tissue. This new device may be useful for evaluating the cornea during experimental animal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 43 publications
(18 reference statements)
9
56
1
Order By: Relevance
“…The HRT II/RCM (Heidelberg Engineering GmbH, Heidelberg, Germany) in vivo confocal microscope for animal studies was used as reported. 37 Briefly, after anesthesia, the rats were positioned sideways under the objective. Several confocal microscopic images of the conjunctival vessels of each eye were taken.…”
Section: In Vivo Confocal Microscopymentioning
confidence: 99%
“…The HRT II/RCM (Heidelberg Engineering GmbH, Heidelberg, Germany) in vivo confocal microscope for animal studies was used as reported. 37 Briefly, after anesthesia, the rats were positioned sideways under the objective. Several confocal microscopic images of the conjunctival vessels of each eye were taken.…”
Section: In Vivo Confocal Microscopymentioning
confidence: 99%
“…The use of this microscope has been previously described [19, 20]. Before in vivoconfocal microscopy examination, animals were intramuscularly anaesthetized with xylazine 2 mg/kg body weight and ketamine 50 mg/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
“…The 3-dimensional organization of the keratocyte network has already been investigated in detail, especially on confocal microscopy. [17][18][19][20][21] The keratocyte cell density is highest in the anterior stroma, and the keratocytes have long processes forming a dense keratocyte network so that the absence of interfibrillar cross-links because of the keratocyte spaces should be significant. The formation of intrafibrillar cross-links as evidenced by the increase in fiber diameter after cross linking 22 should not be affected by this phenomenon, however.…”
Section: Discussionmentioning
confidence: 99%